Role of Аntenatal Antigen Impact on Cardiovascular System Morphogenesis - Yu.G. Reznichenko; A.N. Lebedinets; N.A. Voloshin (Zaslavsky O.Yu., 2013)
In this paper we consider the state of the cardiovascular system in infants with congenital toxoplasmosis without congenital heart disease, carditis (as a model of antenatal antigenic exposure) and features of morphogenesis in rat heart after exposure to antigens in the antenatal period. The study included 38 infants: 18 with congenital toxoplasmosis and 20 healthy. An experimental study of the morphogenesis of the heart of Wistar rats after intrauterine injection of antigens by the method of N.A. Voloshin. Results. According to Doppler echocardiography in children with congenital toxoplasmosis without congenital heart disease, carditis we detected signs of concentric remodeling of the left ventricle with an increase in relative wall thickness, mass and mass index of left ventricular myocardium. In the experiment we established changes in the structure of rat hearts with a significant reduction in the area occupied by cardiomyocytes, in time from 7th till 45th day and with maintaining the downward trend in this indicator to 60th day against the significant increase in the proportion occupied by the connective tissue component, with a significant reduction in the ratio of cardiomyocytes and connective tissue component of the ventricles of the heart from the 1st till 60th day of postnatal development. Conclusions. These features indicate the change of heart morphogenesis after prenatal antigen exposure and are the background for formation of the pathology of the cardiovascular system in children.